Manajemen Pemberdayaan Guru Dalam Meningkatkan Mutu Pendidikan - Sasmita Nurcahaya, Endang; Harris, Taufiq; Furqon Wahyudi, M. (Science and Education Journal (SICEDU), 2026)
Education is not only aimed at transferring knowledge but also at shaping character, skills, and life values. In this context, principals and teachers play an important role in developing teacher empowerment management to improve the quality of learning. However, there are still schools that have not optimized teacher empowerment, which affects the quality of education. This study aims to analyze the management of needs, the process of teacher empowerment, and its impact on improving the quality of education at UPT SDN Margorejo. The research method used is qualitative.The results show that teacher empowerment can be implemented through various programs, such as training in deep learning-based instructional strategies, professional development, strengthening school leadership, and creating a supportive work environment. These efforts have been proven to improve the quality of education.